ROLE OF INTERHEMISPHERIC ASYMMETRIES IN STRUCTURE OF MNEMONIC CAPACITY OF TALENTED ADOLESCENTS: METHODOLOGICAL AND DIAGNOSTIC ASPECTS - Hristina V. Belasheva (Вестник Северо-Кавказского федерального университета)
The article offers a methodological basis for investigating the role of interhemispheric asymmetries in the multi-level structure of mnemonic capacities as indicators of the general talent in nowadays children. There is an empirical research programme introduced as well as neuro-psychological and psycho-diagnostic models methods presented. There is also a view on some new models for differential diagnostics of talents based on neuro-psychological markers and mnemic ability indicators